Cylinder components Properties, applications, materials. (ATZ/MTZ-Fachbuch, 2016)
Owing to the ever-increasing requirements to be met by gasoline and diesel engines in terms of CO2 reduction, emission behavior, weight, and service life, a comprehensive understanding of combustion engine components is essential today. It is no longer possible for professionals in automotive engineering to manage without the corresponding expertise, whether they work in the field of design, development, testing, or maintenance. This technical book provides in-depth answers to questions about design, production, and machining of cylinder components. In this second edition, every section has been revised and expanded to include the latest developments in the combustion engine. Content Piston rings Piston pins and piston pin circlips Bearings Connecting rods Crankcase and cylinder liners Target audience Engineers in the field of engine development and maintenanceLecturers and students in the areas of mechanical engineering, engine technology, and vehicle constructionAnyone interested in technology Publisher MAHLE is a leading international development partner for the automotive industry. With its products for combustion engines and their peripherals as well as for electric vehicles, the group addresses all the crucial issues connected to the powertrain and air conditioning technology: from engine systems and components to filtration to thermal management.